Peran Pondok Pesantren dalam Menanamkan Jiwa Nasionalisme kepada Santri Generasi Z di Pondok Pesantren Sunan Bonang Panca Mulya Tulang Bawang Lampung - Sidiq, Ahmad; Muntaha, Tohir; Subiantoro, Subiantoro (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2025)
Instilling nationalistic values in Generation Z at Islamic boarding schools faces significant challenges amid rapid technological development and globalization. Many Generation Z students are strongly exposed to global culture through social media, which has weakened their orientation towards national values. Although Islamic boarding schools play a central role in character education, research examining how Islamic boarding schools can effectively instill nationalism in Generation Z is still very limited. This study aims to identify the role of the Sunan Bonang Panca Mulya Islamic Boarding School in instilling a spirit of nationalism in Generation Z students and to reveal the challenges faced in the process. The method used in this study is a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and analysis of documents related to national education programs. The results of the study show that although the pesantren has integrated nationalism education into the curriculum, several major challenges, such as low interest in history and limited technological facilities, remain obstacles to effective implementation. This study contributes by offering recommendations on innovations in technology-based nationalism teaching, as well as the use of social media as a more attractive means of national education for santri.